2019
DOI: 10.3233/dev-200001
|View full text |Cite
|
Sign up to set email alerts
|

Coping with Broken Achievement-Related Expectations in Students from Elementary School: An Experimental Study

Abstract: The experiment analyzed reactions of 115 first-to fourth-graders after realizing that they performed worse than they expected in a computer game. Based on the VIOLEX model of expectation violation, we assessed immunization against achievement feedback, assimilation (striving to increase performance), and accommodation (willingness for expectation change). Students decreased their expectations for the next round of the game after getting feedback indicating that they performed worse than expected, and younger s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

5
1

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 26 publications
3
14
1
Order By: Relevance
“…The authors suggested that sex differences in socialization may make girls more sensitive to negative achievement-related feedback. However, a recent study found no sex differences for expectation change after a worse-thanexpected achievement (Pinquart & Block, 2020). Thus, boys' and girls' expectation changes in response to achievement-related feedback might have become more similar in recent years.…”
Section: Age and Sex Differences In Reactions To Disconfirmed Achievement Expectationsmentioning
confidence: 90%
See 3 more Smart Citations
“…The authors suggested that sex differences in socialization may make girls more sensitive to negative achievement-related feedback. However, a recent study found no sex differences for expectation change after a worse-thanexpected achievement (Pinquart & Block, 2020). Thus, boys' and girls' expectation changes in response to achievement-related feedback might have become more similar in recent years.…”
Section: Age and Sex Differences In Reactions To Disconfirmed Achievement Expectationsmentioning
confidence: 90%
“…In the study by Pinquart and Block (2020), children's reported immunization against the negative discrepant feedback was followed by less frequent expectation change. In contrast, reported assimilative and accommodative tendencies did not predict expectation change.…”
Section: Associations Of the Violex Processes With Expectation Changementioning
confidence: 98%
See 2 more Smart Citations
“…Often enough, however, they do not update their expectations when violated by disconfirming evidence Rief et al, 2015;Roese & Sherman, 2007). On the one hand, such expectation maintenance can be advantageous, for example, when disregarding probable noise (Hohwy, 2017), avoiding or attenuating negative affect after worse-than-expected experiences , or protecting expectations that are relevant for values, goals, and positive beliefs that individuals hold about themselves or about the world (Greve & Wentura, 2010;Pinquart & Block, 2020). On the other hand, the maintenance or even stabilization of expectations despite disconfirming evidence -in other words, not adjusting one's internal model of the world to reality -can have negative consequences for oneself (e.g., psychopathology; Craske et al, 2014;Kube et al, 2019Kube et al, , 2020 or others (e.g., stereotypes; Dort et al, 2020aDort et al, , 2020bKotzur & Wagner, 2021).…”
Section: Introductionmentioning
confidence: 99%